Breaking Through Customary Domination for Child Protection: An Analysis of the Gerakan Anti-Merarik Kodeq (GAMAK) from the Perspective of Maqasid al-Shariah - Nunung Susfita; Darmini Darmini; Lukman Santoso (Hukum Keluarga Islam IAIN LANGSA, 2025)
Underage marriage remains a serious challenge in many countries, including Indonesia, where it is complicated by the intersection of legal regulations and customary norms. In Lingsar District, this practice persists through the Merarik kodeq tradition, which is deeply embedded in local culture. Within this context, this study aims to explain the implementation of the Gerakan Anti-Merarik Kodeq (GAMAK) as a community-based prevention strategy and to analyze it through the framework of Maqasid al-Shariah. This qualitative research employed a fieldwork-based approach using methods such as observation, in-depth interviews with 14 key informants, and document analysis conducted over a seven-month period from March to September 2022. The findings reveal that GAMAK is not merely a technocratic policy but has evolved into a transformative social movement that redefines the relationship between custom, religion, and the state. Unlike legal-formal approaches, GAMAK successfully presents an alternative narrative that positions religious and customary leaders not as opponents of the law, but as agents of change who reform local values from within. By embedding anti-underage marriage messages in Friday sermons, women's forums (PKK), and even in village awiq-awiq (customary regulations), GAMAK demonstrates that collective behavioral change can be achieved through grounded and contextual approaches. Viewed through the lens of Maqasid al-Shariah, GAMAK upholds the protection of the five essential principles of Islamic law—religion, life, intellect, lineage, and property—while opening space for negotiation between customary norms and Islamic law in favor of public welfare. The findings show that preventing underage marriage requires transforming entrenched customary norms through collaboration between community leaders, religious authorities, and state institutions. This study contributes to the discourse on legal pluralism and Maqasid al-Shariah in child protection, while offering a practical model for policymakers to replicate in regions with strong customary traditions.